Influence of heat sources and relaxation time on temperature distribution in tissues - Sharma, Kunal; Sharma, S. (Zielona Góra: Uniwersytet Zielonogórski)
In the present study, the temperature fluctuations in tissues based on Penne`s bio-heat transfer equation is investigated by applying the Laplace and Hankel transforms. To get the solution in a physical form, a numerical inversion technique has been applied. The temporal and spatial distribution of temperature is investigated with the effect of relaxation time and is presented graphically.
Keywords: Penne`s bio-heat equation; relaxation time; heat source; Laplace transform; Hankel transform